Comparative Study of The Use of Alum Water as Vulva Hygiene Therapy in Postpartum Mothers - Pearly Otis Putri Oktaviani; Norma Mardiani; Siti Juariah (Majalah Kesehatan Indonesia, 2022)
The maternal mortality rate according to the IDHS (2020) 2020 was 416 cases. West Java showed that the incidence of puerperal fever was still relatively high at around 23%, of all puerperal fever 46% could be identified as infection. The purpose of this study was to determine a comparative study of the use of alum water as therapy for vulva hygiene in mothers. This type of research is a true experimental design with a control group pre and post-test. The population is all postpartum mothers during the early postpartum period for the period June 2022 as many as 205 people. The sampling technique in this study used purposive sampling of as many as 32 postpartum mothers. The results showed that the average postpartum mother respondents who did Vulva hygiene therapy had a greater effect on the intervention group, 6.00 compared to the control group, 2.00, with a 95% confidence level (<0.05), p-value <0.0001, the intervention group with a standard deviation of 0.403. , lower 5.97 and upper 6.40 control group with a standard deviation of 1.078, lower 1.74 and upper 2.89 with a value of Z = -3.564b, p-value <0.0001 then Ha is accepted, meaning that there is a difference between the intervention group and the control group who perform therapy vulva hygiene. Postpartum mothers can take advantage of various kinds of natural ingredients that are around the environment, so they do not require expensive costs and side effects due to chemical-based drugs.